Exploring consumer-brand engagement in online environments designed for tourism - Bilro, R.G. (2022)
The purpose of this study is to present the role of consumer-brand engagement in the online environment designed for tourism. We explore the consumerbrand engagement construct, in relation to consumers as the engagement subjects and brands (i.e. brands/companies) as the engagement objects. This study starts with an extensive and comprehensive literature review, followed by a qualitative study applying focus group techniques to two distinct panels. As a result, we intend to provide a comprehensive understanding of consumer-brand engagement in the online tourism environment. Our aim is to contribute to advancing the theoretical knowledge of this subject and to provide useful insights that can be used by practitioners, particularly those working in the area of touristic brands, who use interactive platforms to create consumer-brand relationships.